2017
DOI: 10.3389/fnins.2017.00252
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Ventricular Arrhythmogenesis with Neuronal Remodeling of Cardiac Postganglionic Parasympathetic Neurons in the Late Stage of Heart Failure after Myocardial Infarction

Abstract: Introduction: Ventricular arrhythmia is a major cause of sudden cardiac death in patients with chronic heart failure (CHF). Our recent study demonstrates that N-type Ca2+ currents in intracardiac ganglionic neurons are reduced in the late stage of CHF rats. Rat intracardiac ganglia are divided into the atrioventricular ganglion (AVG) and sinoatrial ganglion. Only AVG nerve terminals innervate the ventricular myocardium. In this study, we tested the correlation of electrical remodeling in AVG neurons with ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Our recent study has demonstrated that the occurrence of lethal ventricular arrhythmias is accompanied by reduced N‐type Ca 2+ currents in AVG neurons and blunted ventricular vagal activity in coronary artery ligation‐induced CHF rats 26. In the present study, although in vivo transfection of Ca v 2.2‐α shRNA into AVG neurons significantly decreased expression and ion currents of N‐type Ca 2+ channels in ventricular vagal neurons and blunted ventricular vagal activity, it merely induced spontaneous PVCs but not lethal ventricular arrhythmias such as VT/VF in conscious rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our recent study has demonstrated that the occurrence of lethal ventricular arrhythmias is accompanied by reduced N‐type Ca 2+ currents in AVG neurons and blunted ventricular vagal activity in coronary artery ligation‐induced CHF rats 26. In the present study, although in vivo transfection of Ca v 2.2‐α shRNA into AVG neurons significantly decreased expression and ion currents of N‐type Ca 2+ channels in ventricular vagal neurons and blunted ventricular vagal activity, it merely induced spontaneous PVCs but not lethal ventricular arrhythmias such as VT/VF in conscious rats.…”
Section: Discussionmentioning
confidence: 99%
“…The skin was first shaved and sterilized. After laparotomy was performed at the linea alba (abdomen), the radiotelemetry ECG transmitter 26 (TRM54PB, Millar Instruments, Houston, TX) was placed into the abdominal cavity and secured to the abdominal wall at the best position for battery recharging and signal communication. In accordance with the Millar User Manual for ECG recording, bipolar electrodes were tunneled subcutaneously.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remodelling of neuronal function and altered synaptic plasticity have been implicated in myocardial infarction and in wide spectrum of neurological diseases [10]. In order to understand the role of the intracardiac nervous system, many studies have investigated the morphology, neurochemistry and function of intracardiac neurons and intracardiac nerves of various animal models [1][2][3]8].…”
Section: Introductionmentioning
confidence: 99%